Determinants of youth unemployment in Sri Lanka - Fernando, D.N.P. (University of Colombo, 2015)
Youth unemployment is one of the most pressing economic and social problems in Sri Lanka. Recent levels of youth unemployment are found in the context of reduced labour market inflexibilities, an expansion of manpower development through training and development opportunities and higher education as well as social, emotional and economical support of longterm unemployed youth in the country. This study examinesthe determinants of unemployment among youth in Sri Lanka.A cross sectional research design and a mixed methodological approach was applied to use qualitative and quantitative methods as sources of primary and secondary data. Data for this study were mainly obtained from the Sri Lanka Labour Force Survey 2012 collected by the Department of Census and Statistics of Sri Lankajln addition, qualitative data gathered from case studies were also employed.
Keywords: Sri Lanka, unemployment, youth